Plan exportador para la empresa Gelatina Victoriana desde el municipio de Andalucia-Valle del Cauca hacia el mercado internacional (2012)
The Exporter Plan addressed to the Gelatinas Victorianas del Valle Company is developed and carried out in order to promote the international purchase of these products, expand the access of external markets and strengthen the competitiveness producing in this way a better source of employment and increase and keep its participation in the market. The project that is being developed is the design of an exporter plan for the eighteen unit jellies of the following flavors: white, coffee and fruits; which are made based on animal collagen, popularly known in Colombia as calf’s hoof. The Plan is elaborated for the Gelatinas Victorianas Company, a business located in the Andalucía town, Valle del Cauca; the target country is yet to be defined, although knowing the customs of the region, the Latin American countries would be analyzed to export the products previously mentioned. Also, there is the need to develop the corresponding studies, establish the improvement factors to accomplish all the requirements demanded at the time of exporting a product. For achieving this, the exporter plan is composed by phases that allow determining all the issues needed to improve the productivity of the three types of white jellies of the Gelatinas Victorianas Company and turning this business into a well-known exporter company in the international market. In the exporter plan the company and the market are studied. Likewise, it is also analyzed the relation between them from different points of view such as the administrative divisions, the productivity capacity, the financial situation, the product and its competitiveness. Regarding the market, it is analyzed aspects such as the exportation targets, the competitors, consumers and the paths of distribution. To sum up, with all of these the final goals to achieve are determined, and it is alsoestablished an action plan as well as the strategies to carry it out.